2003
DOI: 10.2527/2003.8192333x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and diet affect glucose dynamics and insulin sensitivity in Thoroughbred geldings1

Abstract: Insulin resistance is considered a risk factor in obesity, laminitis, exertional rhabdomyolysis, and osteochondrosis. The objective was to use the minimal model to estimate glucose effectiveness (Sg) and insulin sensitivity (Si) in nonobese to obese horses initially adapted to forage only, then adapted to forage plus supplements rich in starch and sugar (SS) or fiber and fat (FF). Ten Thoroughbred geldings, with BCS of 5 (nonobese), 6 (moderately obese), and 7 to 8 (obese), were adapted to pasture and hay, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
279
5
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(314 citation statements)
references
References 43 publications
21
279
5
9
Order By: Relevance
“…Similar to our findings, higher glucose and insulin responses were reported in aged horses (.20 years) than in young horses (,5 years) after an oral glucose challenge (Ralston et al, 1988;Malinowski et al, 2006). Recent research indicates a negative impact on insulin sensitivity in horses fed high glycaemic meals over a period of months (Hoffman et al, 2003;Treiber et al, 2005). In the present study before the start of experiments, the young horses were mainly on a grass-or hay-based diet with less exposure to starch.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Similar to our findings, higher glucose and insulin responses were reported in aged horses (.20 years) than in young horses (,5 years) after an oral glucose challenge (Ralston et al, 1988;Malinowski et al, 2006). Recent research indicates a negative impact on insulin sensitivity in horses fed high glycaemic meals over a period of months (Hoffman et al, 2003;Treiber et al, 2005). In the present study before the start of experiments, the young horses were mainly on a grass-or hay-based diet with less exposure to starch.…”
supporting
confidence: 89%
“…In most studies, a 10-to 18-h overnight fast is described, and no additional forage was given to the horses during the postprandial blood sampling period (Stull and Rodiek, 1988;Vervuert et al, 2003Vervuert et al, , 2004Vervuert et al, , 2007Vervuert et al, , 2008aVervuert et al, , 2008bVervuert et al, and 2008cJose-Cunilleras et al, 2004;Zeyner et al, 2006). In other studies, ad libitum access to hay was offered the night before and during the blood sampling procedure (Hoffman et al, 2003;Treiber et al, 2005). The data from literature provide evidence that the feeding state before feeding of the test diet might influence the glycaemic and insulinaemic responses.…”
Section: Introductionmentioning
confidence: 99%
“…Pratt et al (2006) reported a 30% decrease in insulin-dependent glucose uptake in horses fed a diet rich in non-structural carbohydrates, compared to horses fed a diet containing fibre and fat, in which sensitivity to insulin did not change. Similar results were obtained by Hoffman et al (2003), who found that sensitivity to insulin tended to decrease in horses fed a supplement rich in starch and carbohydrates.…”
Section: Mechanisms Of Insulin Resistancesupporting
confidence: 77%
“…Chronic hyperglycaemia, hyperinsulinemia, and disturbed glucose transport into the cells will aggravate tissue IR (Kahn & Flier 2000;Vick et al 2007). Research has shown that insulin sensitivity in obese horses is 80% lower than in horses with normal body weight (Hoffman et al 2003).…”
Section: Role Of Adipose Tissue In Irmentioning
confidence: 99%
“…However, considering the faithful fulfilment of the original scale described by Henneke et al (1983), the results confirm that the scores to designate these two body categories (obese and overweight) should be raised at least in Andalusian horses. Previous studies in which the conventional body scoring system has been utilized, obese horses have been described using different cutoff values (Gentry et al, 2002;Hoffman et al, 2003;Gentry et al, 2004;Buff et al, 2006;Frank et al, 2006;Vick et al, 2006;Waller et al, 2006;Ungru et al, 2012). This lack of consensus among different researches to define obesity stands out the relevance of these results where based strictly on an objective appraisal of the body condition (SFT ultrasonography) and in accordance with a quantitative corroborated obesity variable (%BF) it has been possible to fix concrete cut-off values adjusted to a specific breed.…”
Section: Discussionmentioning
confidence: 99%